The effect of monetary incentives on individual and organizational performance in an Italian public institution - Gian Carlo Cainarca; Francesco Delfino; Linda Ponta (Administrative Sciences, 2019)
This paper addresses the role of monetary incentives with regard to the performance of employees and organizations. The distribution of monetary incentives among employees in public administration has been investigated. Specifically, the traditional approach of bureaucracy that pays a premium to each employee, based on the position held, is compared with a merit approach which tends to recognize and reward individual contributions. A task advice centrality indicator and a value index have been defined and used to study the performance of employees. The results show a modification of individual behaviors, in line with the theoretical foundations and predictions formulated.
Keywords: 350; monetary incentives; organization; public administration; networks